When AIE meets enzymes. Issue 18 (5th August 2022) - Feng, Guangfu; Liao, Sijie; Liu, Yufeng; Zhang, Huaizu; Luo, Xingyu; Zhou, Xiangming; Fang, Jun
Abstract : Applications of AIEgens in biosensing, disease diagnosis, and drug release. Abstract : With the rapid development of physiopathology and the surge in demand for comprehension of micro-scale physiological events, AIE-based bio-probes are found superior in presenting precise and practical results in enzyme imaging and analysis with a high signal-to-noise ratio and non-destructive operation. By delivering enzyme-responding "light-up" fluorescence signals, the visual and real-time tracking of the distribution and activity of intracellular enzymes is accomplished with AIE-based bio-probes. In particular, by combining with modern nano-encapsulation technologies, AIE-based compounds can realize the simultaneous diagnosis and treatment of specific diseases that are difficult to deal with through traditional strategies. This review summarizes and generalizes the typical AIE-based bio-probes reported recently based on the AIE mechanisms of solubility changes, excited-state intramolecular proton transfer (ESIPT), electrostatic interactions, and hydrophobic interactions, expounding their great values in the bio-sensing and bio-medicine field. Advanced enzyme detection and estimation, cell identification, disease diagnosis, and controlled drug release are demonstrated with high confidence and reproducibility. Through the in-depth analysis of these bio-probes' design and working principles, currently existing drawbacks and further future directions are subsequently proposed to promote a more prosperous development of AIE-based enzyme probes.